From Employment Quotas to Enforceable Inclusion: Comparing Disability Employment Governance in Indonesia, the Philippines, and Germany - Benedicta Mary Tiara Florensia Patient Sudin; Muh. Ali Masnun; Wira Satya Nugraha Wicaksono; Princess Alyssa D. Tee-Anastacio (RechtIdee, 2026)
Study Objective: This study analyzes the legal certainty for workers with disabilities in Indonesia based on the Law on Persons with Disabilities and compares the legal and policy approaches implemented by three countries for workers with disabilities.Methods/Approach: This study employed a normative legal research method, employing statute, conceptual, and comparative approaches, supported by primary legal materials, secondary legal materials, and non-legal materials collected through desk research and analyzed using prescriptive analysis.Novelty: This study focuses on the Indonesian legal framework, which does not provide legal certainty for workers with disabilities because there are no sanctions against companies that fail to fulfill their obligations to provide employment opportunities for people with disabilities.Findings: Indonesia does not yet have binding regulations on companies that fail to provide employment opportunities for workers with disabilities. The Philippines has provided tax incentives for companies that recruit workers with disabilities. In contrast, Germany has the strongest legal system, imposing fines on companies that do not employ workers with disabilities.Conclusion: Indonesia needs to immediately enact strict, binding implementing regulations to create optimal employment opportunities for workers with disabilities.